1990
DOI: 10.1346/ccmn.1990.0380211
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Aluminum on Iron Oxides: XIV. Al-Substituted Magnetite Synthesized at Ambient Temperatures

Abstract: Abstract--Mixtures of magnetite and goethite were formed by the slow oxidation of mixed FeCI2-A1C13 solutions in an alkaline environment at room temperature. The compositions of the products ranged from almost exclusively magnetite in Al-free systems to goethite only at AI/(A1 + Fe) ~ 0.3. The magnetic phase consisted of a partly oxidized (Fe2+/Fe 3+ < 0.5), Al-substituted magnetite. The unit-cell edge length a of the magnetite decreased with increasing A1 (Al = 0-0.37 per formula unit, corresponding to 0-14 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 16 publications
3
33
0
Order By: Relevance
“…XRD data for the powder MT-RT-00 with Als = 0.001 along with those of its heated products is shown in Figure 3. Goethite content increased with increase in Als for the MT-RT series in agreement with a similar effect reported by Schwertmann and Murad (1990). Mean crystallite dimensions (MCDs) for magnetite (unheated powders) and hematite (500~ powders) were calculated using the Scherrer equation (Zussmann, 1977).…”
Section: Total Chemical Analysis and Xrdsupporting
confidence: 81%
See 1 more Smart Citation
“…XRD data for the powder MT-RT-00 with Als = 0.001 along with those of its heated products is shown in Figure 3. Goethite content increased with increase in Als for the MT-RT series in agreement with a similar effect reported by Schwertmann and Murad (1990). Mean crystallite dimensions (MCDs) for magnetite (unheated powders) and hematite (500~ powders) were calculated using the Scherrer equation (Zussmann, 1977).…”
Section: Total Chemical Analysis and Xrdsupporting
confidence: 81%
“…The magnetites are, therefore, strongly cation deficient (partially oxidized). This is apparently the general case for magnetite prepared by wet chemical methods (Schwertmann and Murad, 1990;Sidhu et aL, 1981). Upon heating the magnetite powders to 400~ for 4 hr in the air, the Fe 2 § was completely oxidized to Fe 3 § ( Figure 2).…”
Section: Total Chemical Analysis and Xrdmentioning
confidence: 66%
“…Because the rate of oxidation of Fe 2+ increases with increasing pH (Stumm and Lee, 1961), a pH increase from 7 to 8 might have favored lepidocrocite. At the same time, the formation of magnetite-maghemite, which is very likely at this pH, might have been suppressed by A1 (Schwertmann and Murad, 1989;Taylor and Schwertmann, 1978).…”
Section: Methodsmentioning
confidence: 92%
“…In the inverse spinel structure, the trivalent cations occupy both tetrahedral and octahedral sites. The Si 4+ ion prefers a tetrahedral site (Newberry et al, 1982), as does the Al 3+ ion (Schwertmann and Murad, 1990). Although De Sitter et al (1977) concluded that the Ca 2+ ion prefers a tetrahedral site, we have followed recent studies (e.g., Shiga, 1989;Westendorp et al, 1991), in which the Ca 2+ ion is assigned to an octahedral site.…”
Section: Table 3 (Continued)mentioning
confidence: 88%